Predictors of cardiovascular disease in patients with type 2 diabetes mellitus - Tan, Mun Ching; Wong, Teck Wee; Chan, Yoke Mun; Joseph A.,; Abdul Rahman, Hejar; Ng, Ooi Chuan (DRUNPP, 2013)
Aims: Cardiovascular disease (CVD) is the leading cause of mortality and morbidity in patients with type 2 diabetes mellitus (T2DM). Although patients with T2DM and CVD share common risk factors, the link between these diseases remains unclear. This study intends to identify the predicting risk factors of CVD in Malaysian T2DM patients. Methods: We conducted an analytical cross-sectional study on 313 patients diagnosed withT2DM at selected tertiary hospitals upon prior ethical approvals. Systematic random sampling method was applied in patient selection. Socio-demographic data was assessed using a pre-tested interviewer-administered structured questionnaire. Diet (by 24-hour dietary recall), physical activity level [via International Physical Activity Questionnaire (IPAQ)], smoking andalcohol consumption status were ascertained. Anthropometric and blood pressure measurements were performed according to standard procedures. Clinical and laboratory characteristics on cardiovascular risk factors (medical history, treatments, glycaemic control,and lipid profile) were collected from medical records, clinical examination and face-to-face interview. All statistical analyses were performed by using SPSS Statistics Version 21.0. Results: The mean age of study subjects was 55.7±9.2 years, with a mean diabetes duration of 10.1±8.1 years (CVD patients 11.5±8.7 years, non-CVD patients 9.2±7.6 years); 52.1%subjects were females; and 47.0% were Malays. Approximately one third (36.1%) of thesubjects were suffering from CVD. Multivariate logistic regression analysis showed age(B=0.056, adjusted OR 95% CI=1.058, p=0.004), lower HDL-C level (B=-1.466, adjusted OR 95% CI =0.231, p=0.003), working status of self-employment (B=1.381, adjusted OR 95% CI=3.978, p=0.002) in comparison to retirement, low (B=1.164, adjusted OR 95% CI=3.203, p<0.001) andmoderate physical activity levels (B=1.172, adjusted OR 95% CI=3.227, p<0.001) compared tohigh physical activity level were significantly associated with higher CVD risk, uponadjustment for potential covariates. Conclusion: Increased age, lower HDL-C, low and moderate physical activity levels, andworking status appeared to be significant predictive factors of CVD among the T2DM patients studied.